ANALISIS PENGARUH LITERASI KEUANGAN DAN SIKAP KEUANGAN TERHADAP PERILAKU MANAJEMEN UMKM DI KOTA MAKASSAR - Tonapa, Cindy Dewi Cristin; Todingbua, Manuel A.; Mongan, Claudio Julio (ANALISIS, 2025)
The need for careful financial management in order for MSMEs to adjust and prosper in a cutthroat market is what motivates this study. Effective financial management is frequently a challenge for MSMEs with inadequate financial literacy and proper financial attitudes. This study looks into how financial attitudes and financial literacy affect MSMEs' financial management practices in Makassar City. Questionnaires were used to gather data as part of a quantitative research approach. The findings indicate a significance level of 0.000, which is less than 0.05, and a F value of 18.749, which is higher than the F table value of 3.091. This indicates that the financial behavior variable is highly influenced by financial attitudes and financial knowledge. According to the analysis conducted with SPSS 26, financial attitudes and financial literacy have a major influence on the financial management behavior of MSMEs in Makassar City.